2013
DOI: 10.1002/ajh.23451
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of European APL 2000 trial, evaluating the role of cytarabine combined with ATRA and Daunorubicin in the treatment of nonelderly APL patients

Abstract: All-trans retinoic acid (ATRA) combined to anthracycline-based chemotherapy is the reference treatment of acute promyelocytic leukemia (APL). Whereas, in high-risk patients, cytarabine (AraC) is often considered useful in combination with anthracycline to prevent relapse, its usefulness in standard-risk APL is uncertain. In APL 2000 trial, patients with standard-risk APL [i.e., with baseline white blood cell (WBC) count <10,000/mm 3 ] were randomized between treatment with ATRA with Daunorubicin (DNR) and AraC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…The complete remission rate of APL exceeded 90% with the application of all-trans retinoic acid (ATRA), arsenic trioxide (ATO), and anthracycline-based chemotherapy [2]. However, the 7-year cumulative incidence of relapses was reported as 28.6% in APL maintenance with ATRA and daunorubicin [3] and even reached 33% in the ATRA maintenance treatment group [4]. The relapse/refractory patients showed resistance to ATRA and/or ATO, which has been identified as a clinically significant problem.…”
Section: Introductionmentioning
confidence: 99%
“…The complete remission rate of APL exceeded 90% with the application of all-trans retinoic acid (ATRA), arsenic trioxide (ATO), and anthracycline-based chemotherapy [2]. However, the 7-year cumulative incidence of relapses was reported as 28.6% in APL maintenance with ATRA and daunorubicin [3] and even reached 33% in the ATRA maintenance treatment group [4]. The relapse/refractory patients showed resistance to ATRA and/or ATO, which has been identified as a clinically significant problem.…”
Section: Introductionmentioning
confidence: 99%
“…Daunorubicin, an anthracycline produced by Streptomyces peucetius [92], has been extensively used for the treatment of acute promyelocytic leukemia by acting through epigenetic inactivation of genes in the INK4/CDK/RB cell cycle pathway [93,94], and other cancer therapies [95,96], as well as against unwanted intraocular proliferation [97]. However, its anticancer effects have been related to inhibition of DNA topoisomerase II [98].…”
Section: Contact Patterns At Distances Less Than 4 åmentioning
confidence: 98%
“…Patients \60 years and with standard risk (WBC count B 10 9 10 9 /L) were randomized into Ara-C and no Ara-C groups in induction and consolidation therapies. The results showed that DNR alone instead of the classic DNR-Ara-C combination led to a higher risk of relapse, with the 7-year cumulative incidence of relapses (CIR) 28.6 % in the non-Ara-C group, compared to 12.9 % in the Ara-C group (P = 0.0065) [47].…”
Section: Ato In Consolidation Therapymentioning
confidence: 99%